2012
DOI: 10.1002/gcc.21982
|View full text |Cite
|
Sign up to set email alerts
|

High detection rate of clinically relevant genomic abnormalities in plasma cells enriched from patients with multiple myeloma

Abstract: Multiple myeloma is a heterogeneous disease, which is characterized by the occurrence of specific genomic abnormalities that are both of diagnostic and prognostic relevance. Since the detection of these abnormalities through molecular‐genetic techniques is hampered by the overall low percentage of plasma cells present in primary bone marrow aspirates, we assessed the efficacy of these techniques in enriched plasma cell fractions from 61 multiple myeloma patients. Using interphase FISH, genomic abnormalities co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The chromothripsis-like pattern has been commonly observed in 1q, 13q, and 16q as compared to the chromothripsis-like pattern confirmed in this study and similar results in other studies [22, 45]. Unlike the result from other studies, chromothripsis-like patterns in 2q, 3q, 10q, 12q, and 17p were not observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…The chromothripsis-like pattern has been commonly observed in 1q, 13q, and 16q as compared to the chromothripsis-like pattern confirmed in this study and similar results in other studies [22, 45]. Unlike the result from other studies, chromothripsis-like patterns in 2q, 3q, 10q, 12q, and 17p were not observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…One of the major disadvantages of FISH method is the dependency to the quantity of bone marrow plasma cell percentage. Interphase FISH method with plasma cell enrichment by CD 138 labelling rather than examining on cultured bone marrow samples are suggested for higher detection rates of genetic abnormalities 8,9 . To date, European Myeloma Network recommends Interphase FISH method for MM and states as acceptable, till plasma cell enrichment methods becomes more accessable and less costly 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the simultaneous measurement of signal intensity of each probe when compared to a normal reference together with the differentiation of alleles by genotype analysis of each SNP probe facilitates the determination of ploidy level. The clinical importance of this distinction has been demonstrated in MM patients where the use of genomic array platforms has prevented misinterpretation of a near‐tetraploid status, associated with an intermediate prognosis, with a hyperdiploid status, associated with a relatively good prognosis (Stevens‐Kroef et al, ).…”
Section: Clinical Utilitymentioning
confidence: 99%